Sense of alexithymia in a patient with psoriasis and depression - Ogłodek, Ewa; Marek, Luiza; Araszkiewicz, Aleksander; Placek, Waldemar; Moś, Danuta (Dermatology Review/Przegląd Dermatologiczny, 2009)
Introduction. Sense of alexithymia is a term first proposed by Sifenos to describe disorders in the sphere of expression and perception of the patient’s feelings. Limited abilities of a patient with psoriasis and sense of alexithymia to experience emotions cognitively lead instead to concentration on somatic sensations. This is accompanied by emotional excitement and by poorly controlled compulsive reactions to negative stimulation. Sense of alexithymia in patients with depression and psoriasis is regarded as a personality trait, which, in combination with other features, predisposes to occurrence of emotional disturbances. Objective. Evaluation the sense of alexithymia in a male patient with psoriasis and depression. Case report. A 45-year-old male patient with a 20-year history of psoriasis was 7 times hospitalized in the Department of Dermatology due to typical, very extensive plaque psoriasis. The patient reported many psychological complaints. Psychiatric examination, based on the DSM-IV classification of psychiatric disorders, enabled depression to be diagnosed. Evaluation of sense of alexithymia was performed by a shortened version of the Toronto Alexithymia Scale (TAS-20) and revealed the highest value of the factor “difficulty in communicating one’s emotions to others”. Conclusions. Sense of alexithymia may be a result of long-term stress which, in turn, may be provoked by psoriasis and depression.